The Annual Convention of the Association of Muslim Social scientists (American Journal of Islam and Society, 1999)
The Annual Convention of the Association of Muslim Social Scientists(AMSS), was held at the Graduate School of Islamic and Social Sciencesin Leesburg, VA 29-31 October.By all accounts, this convention was a success and heralds a resurgenceof the Association. The convention generated an air of excitement andexpectations about the Association’s immediate future. Over 150 participantsattended and 70 presentations were made. In addition, the conventionwas graced by nine foreign scholars: two from India, one from Brunei, onefrom Malaysia, three from Canada, one from France, and one from Turkey.The Faruqi memorial lecture was delivered by AbdulHameedAbuSulayman, the president of the International Institute of IslamicThought (IIlT). He focused on the Muslim communities’ need to focus onthe intellectual development of children because it is an important aspect ofthe revival of the ummah. The keynote address at the banquet was given byTariq Ramadan a prominent Muslim social scientist and community leaderfrom France. His talk brought a Efreshing focus to what it means to be anengaged Western Muslim.In many ways this convention was a turning point in the history ofAMSS. Here, the old and the new met and had a meaningfid dialogue aboutthe direction of the Association. The convention also marked a change ofguard as many new and younger Muslim scholars, particularly graduatestudents, joined the board. Faizan Haq, a B.D. student at SUNY Buffalowas elected general secretary and is also in charge of the AMSS outreach ...